Infâq Menurut Perspektif Al-Qur’an - Sulaiman Ibrahim (Jurnal Bimas Islam, 2015)
Abstract Advocated to infaq, to every Muslim to use their property in a way that is good and true. Including by channeling such assets to improve the lives of private and public, to narrow the distance of separation between the rich and the poor. According to the Koran, the property has a social function. When collecting treasures must be halal and good principle, and considering the interests of society. Because the property we have is actually coming from Allah. In which people were given a mandate to use and take care of the property for the benefit of personal, family and community in the frame of devotion to Alah SWT. Abstraksi Pensyariatan infak, mengarahkan setiap muslim agar menggunakan harta mereka dengan cara yang baik dan benar. Di antaranya dengan menyalurkan harta tersebut untuk meningkatkan kesejahteraan hidup pribadi dan masyarakat, mempersempit jarak pemisahan antara si kaya dan si miskin. Menurut al-Qur’an, harta milik itu mempunyai fungsi sosial. Ketika mengumpulkan harta haruslah prinsip halal daan baik, serta memperhatikan kepentingan masyarakat. karena harta yang dimiliki itu sebenarnya hanya pinjaman dari Allah swt. di mana manusia diberi amanat untuk menggunakannya dan mengurus harta itu untuk kepentingan pribadi, keluarga dan masyarakat dalam bingkai pengabdian kepada Allah swt. Keywords: Koran, donation/infaq, concept